Crafting the Machine Mind: A Poiesis Analysis of Artificial Intelligence in Terminator 1 - Tanuraharja, Axel Valens; Prayoga, Kurniawan Agung; Sari, Nara (J-Lalite: Journal of English Studies, 2024)
Terminator 1 is a 1984 science fiction movie about a robot who is sent from the future to kill a person named Sarah Connor, because her son is destined to lead humanity in the war against robots. The movie shows the futuristic depiction of AI technology and their potential capabilities as weapons. The rapid development of AI had also raised some concerns at the time with people worrying about AI being more than capable of surpassing humanity. Although the concept of AI gaining sentience is merely fiction, the application of AI as weapons is something that has become more real with each passing day. This study explores the concept of AI in Terminator 1 using Poiesis or the creation of new ideas from old ones to see how the movie has inspired the evolution of AI in the modern world. Additionally, this study aims to describe the movie's portrayal of AI and compare it to modern AI technology in real life. Through this study we found that the nature of AI is depicted accurately within the movie’s time of release. However, the applications of AI technology were still fictitious.